(untitled) (Shahroud Journal of Medical Sciences, 2020)
Background: Marital relationship has been described as the most important and fundamental human relationship because it provides the basic structure for forming a family relationship and life satisfaction. Also, one of the factors which play an important role in the marital satisfaction of couples is positive feelings towards the spouse, which include both positive emotions. This study aimed to investigate the effect of emotion-focused couple therapy on marital satisfaction and positive feelings towards the spouse. Methods: This semi-experimental method with a pre-and post-test design was conducted on a sample group of 14. The statistical population of the present study includes all married women who in 2018 were referred to counseling centers and neighborhoods in the 10th district of Tehran city. The sampling method in this research is a purposeful sampling. Thus, the questionnaires of enriching and nurturing relationship issues‚ communicating and happiness(ENRICH) and positive feeling questionnaire (PFQ)were completed by married women referring to counseling centers and shelters in the 10th district of Tehran. After scoring the questionnaire, select 14 people who are allowed to score or below average in ENRICH and PFQ. A Paired t-test was used to significantly evaluate the differences between the means in the pre-test and post-test stages. Statistical analysis was conducted using IBM SPSS-24. The significance level was set at 0.05 for all tests. Results: The results of the paired t-test showed that there was no significant difference between the mean scores of the subjects in the pre-test and post-test stages in the variables of marital relationship, relationship with relatives, and friends and spiritual beliefs (Pvalue<0.05), but in There were significant differences in the variables of personality issues, conflict resolution, sexual relations, marriage and children and the total score of marital satisfaction and positive feelings towards the spouse. Conclusions: Emotion-focused couple therapy is effective in marital satisfaction and positive feelings Spouse, hence; family counselors and family therapists can use the results of the present study for therapeutic interventions based on emotion-focused couple therapy to increase marital satisfaction and positive feelings in couples. Keywords: Emotion-focused couple therapy, Marital satisfaction, Positive feelings, Spouse